2014
DOI: 10.1186/1824-7288-40-29
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and socio-demographic factors associated with non-protective immunity against tetanus among high school adolescents girls in Nigeria

Abstract: BackgroundThe low uptake of tetanus vaccine and its resultant high burden of tetanus in Nigeria suggest the need to improve routine and booster vaccination in children and adolescents. However, epidemiological evidence for vaccination in the adolescent age group needed for effective strategy and policy formulation is lacking. This study was carried out to determine the prevalence of protective immunity against tetanus and to identify risk factors for non-protective immunity among schooling adolescents.MethodsU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…This may be a function of their knowledge of the vaccine as found in this study and others [16,28]. While age and educational status were positive predictors for tetanus toxoid uptake in some studies, one study showed an inverse relationship between protective immunity for tetanus and increasing maternal age [29,30]. The differences in findings may be a function of the variation in the studied population characteristics and differences in study designs.…”
Section: Discussionsupporting
confidence: 52%
“…This may be a function of their knowledge of the vaccine as found in this study and others [16,28]. While age and educational status were positive predictors for tetanus toxoid uptake in some studies, one study showed an inverse relationship between protective immunity for tetanus and increasing maternal age [29,30]. The differences in findings may be a function of the variation in the studied population characteristics and differences in study designs.…”
Section: Discussionsupporting
confidence: 52%
“…However, that none of the primiparous mothers who participated in this study could recollect being given tetanus toxoid injection 1-2 years prior to pregnancy calls for public health concern. Given the mean age of the mothers (27.9 years), it was unlikely that many of the mothers had had tetanus toxoid injection during adolescence as a previous study in the same Ibadan reported a very poor immunisation experiences among high school adolescent girls [ 7 ]. It was on the basis of these observations that the investigator counselled the participating mothers and advised the health worker at the primary health facilities to give tetanus toxoid injection to those who tested negative to the TQS test before they were discharged home after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Trained research assistants (nurses and community health officers) administered the questionnaire to mothers and examined neonates within 24 hours after delivery. The various items in the questionnaire were adapted from those used for three previous studies [ 7 9 ], this included socio-demographic characteristics, questions on knowledge and tetanus vaccination history. Knowledge about tetanus was assessed on a 10-point scale, comprising statements and questions (with possible answers as true, false, or I don't know).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, pertussis, also known as whopping cough, is caused by Bortedella pertussis , which can produce loss of weight, subconjunctival hemorrhages, and syncope ( 26 ). Currently these three diseases circulate in the population worldwide and the highest rates are observed in children from countries with low vaccination coverage, especially in developing countries ( 27 29 ). However, and despite high vaccination coverage, several outbreaks have recently been reported in industrialized countries ( 30 ).…”
Section: Vaccines Currently Recommended By the Whomentioning
confidence: 99%